LEGITIMACY FOR ACCOUNTING FOR ENVIRONMENTAL DEGRADATION AND POLLUTION - Enahoro, John A. (European Scientific Journal, ESJ, 2012)
The responsibility of care for natural resource is the owners of natural resource and all stakeholders including the duty of general care to all. Responsibility of care is with the view of minimizing adverse impact of degradation on the natural environment. It is also with the view of mitigating the degradation impact aimed at avoidance of potential contingent costs liability. This study has reviewed theory for the legitimacy for environmental accountability such as The United Nations’ Protocols and agreements on environment and the Kyoto Convention. The study also reviewed the Eco-efficiency framework and models for environmental accounting. Policy recommendations are proffered on corporate governance with respect to effective natural environment responsiveness and accountability towards avoidance of environment contingent costs and liabilities which are encountered by organizations.